2009
DOI: 10.1177/0961000609345090
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing CPD in the Caribbean: Individual quest versus organizational goal

Abstract: This study explores Caribbean librarians’ perceptions on continuing professional development (CPD) as it relates to employer support, personal interest and motivation. CPD literature was reviewed and a questionnaire designed. Hypotheses were tested based upon the following questions: do clearly defined CPD policies motivate librarians to pursue CPD activities?; are librarians motivated to pursue CPD where their organizations have formal programmes?; and are librarians who pursue CPD motivated primarily by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Thus, indicating that most of the participants were motivated to pursue continuing development activities, as only one individual or 4 percent of participants disagreed with the statement. These findings are comparable to other studies such as Tyrell (2015) and Gosine-Boodoo and McNish (2009) which reported a high level of personal motivation amongst librarians to pursue CPD.…”
Section: Discussion Of Findingssupporting
confidence: 89%
See 4 more Smart Citations
“…Thus, indicating that most of the participants were motivated to pursue continuing development activities, as only one individual or 4 percent of participants disagreed with the statement. These findings are comparable to other studies such as Tyrell (2015) and Gosine-Boodoo and McNish (2009) which reported a high level of personal motivation amongst librarians to pursue CPD.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…These findings are supported by Gosine-Boodoo and McNish (2009) which reported that across all categories of Caribbean librarians in academic, special and public libraries, “the top three motivating factors were: learning new skills, technological changes and personal development” (p. 207). It should be noted that motivating factors such as increased salary and other incentives, job promotion and being mandated by employer got the lowest rankings.…”
Section: Discussion Of Findingsmentioning
confidence: 66%
See 3 more Smart Citations